Kompetencje Rady Ministrów w zakresie bezpieczeństwa Rzeczypospolitej Polskiej. Przyczynek do rozważań - Opaliński, Bartłomiej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The article concerns weighty issues of entitlements of the Council of Ministers in the field of the national security. It has contributory character, prompting broader deliberations on the given issue. In the beginning a reconstruction of the position of the Council of Ministers in the system of state agencies of the Republic of Poland was attempted. Next, the general management of the Council of Ministers in the field of the country's defence was analysed on the basis of art. of 146 sec. 4 pt 11 of Polish Constitution. Later, the function and competence of three subjects forming the government: the prime minister, the National Defence minister and the Minister of Internal Affairs were transposed based upon the title issues. Based on made arrangements there were expressed conclusions de lege ferenda.
THE COMPETENCE OF THE COUNCIL OF MINISTERS IN THE REALM OF THE SECURITY OF THE REPUBLIC OF POLAND. A CONTRIBUTION TO DISCUSSIONS
Keywords: Council of Ministers; safety; defence; prime minister; National Defence minister; the Minister of Foreign Cases